Response and remission rates in different subpopulations with major depressive disorder administered venlafaxine, selective serotonin reuptake inhibitors, or placebo - Entsuah, A. Richard; Huang, Holly; Thase, Michael E. (The Journal of Clinical Psychiatry, 2001)
Compared patient age and gender subpopulations on the basis of remission and response rates associated with venlafaxine and selective serotonin reuptake inhibitor (SSRI) treatment. A meta-analysis of original data from 8 comparable double-blind, active-controlled, randomized clinical trials was conducted. Antidepressant efficacy was assessed for 2,045 patients (aged 18-83 yrs) who met Diagnostic and Statistical Manual of Mental Disorders-III-Revised (DSM-III-R) criteria for major depression or Diagnostic and Statistical Manual of Mental Disorders-IV (DSM-IV) criteria for major depressive disorder and were randomly assigned to receive venlafaxine, 1 of several SSRIs, or placebo for up to 8 wks. Symptoms of depression were assessed using the Hamilton Rating Scale for Depression (HAM-D). Remission was defined as a HAM-D-17 score ≤7, response was defined as ≥50% decrease in HAM-D-21 score, and absence of depressed mood was defined as a HAM-D depressed mood item score of 0. Results show no significant age-by-treatment, gender-by-treatment, or age-by-gender-by-treatment interactions; men and women of different ages within a given antidepressant treatment group exhibited similar rates of remission, response, and absence of depressed mood. Remission rates during venlafaxine therapy were higher than during SSRI therapy. Onset of remission was more rapid with venlafaxine than with SSRI treatment. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: Adult; Age Differences; Analysis of Variance; Antidepressive Agents, Second-Generation; Cyclohexanols; Depressive Disorder, Major; Drug Therapy; Drugs; Female; Fluoxetine; Human Sex Differences; Humans; Major Depression; Male; Middle Aged; Randomized Controlled Trials as Topic; Remission (Disorders); Remission Induction; Response Parameters; Reuptake; Serotonin Reuptake Inhibitors; Serotonin Uptake Inhibitors; Venlafaxine; Venlafaxine Hydrochloride; age differences; gender; major depressive disorder; remission rates; response rates; selective serotonin reuptake inhibitor; venlafaxine